Life Cycle Assessment of Strandkorb Beach Chair Production - Fadilah Artanti Rahmania; Dira Ernawati; Sinta Dewi (Indonesian Journal of Innovation Studies, 2026)
General Background: Wooden furniture production relies on raw materials, auxiliary inputs, and energy-intensive operations that may generate substantial environmental pressures. Specific Background: This study assessed strandkorb beach chair production using a gate-to-gate Life Cycle Assessment with SimaPro 9.0 and ReCiPe 2016 (H), covering production stages from raw material use to final factory processes. Knowledge Gap: Although Life Cycle Assessment has been applied in manufacturing and furniture studies, limited work has examined wooden beach chair production by identifying detailed process-level hotspots for practical company improvement. Aims: The study aimed to evaluate environmental burdens from strandkorb beach chair production and determine the production stages contributing most substantially to those burdens. Results: The analysis showed that marine ecotoxicity, freshwater ecotoxicity, and freshwater eutrophication were the most significant midpoint categories, indicating pressure on aquatic ecosystems. At the endpoint level, the total score reached 53.5 Pt, with human health contributing 31.8 Pt, resources 12.9 Pt, and ecosystems 8.77 Pt. The wood kiln drying stage was the main hotspot, contributing 37.1 Pt overall, including 21.7 Pt to human health, 8.43 Pt to ecosystems, and 6.94 Pt to resources, mainly due to high electricity and fuelwood consumption. Novelty: This study provides a gate-to-gate ReCiPe 2016 assessment of strandkorb beach chair production and identifies kiln drying as the critical process hotspot. Implications: The findings support energy efficiency, kiln operation optimization, low-VOC finishing materials, and more sustainable supplier selection as priorities for cleaner production. Highlights: Aquatic toxicity categories showed the highest comparative importance. Human health recorded the largest endpoint score at 31.8 Pt. Energy use and finishing chemicals became priority areas for improvement. Keywords: Beach Chair, Environmental Impact, Life Cycle Assessment, ReCiPe 2016